Partial facial hemihypertrophy: A case report and review of literature - Adity Bansal; Gosla Srinivas Reddy; Ashi Chug (Wolters Kluwer Medknow Publications, 2020)
Hypertrophy of the facial region is rare developmental malformation. The aim of this study is to report a case of partial facial hemihypertrophy describing its clinical features and debatable heterogeneity of etiologies, along with the review of literature to supplement to its current knowledge in English literature. PubMed search was done from 1986 to 2018, using the terms "Partial facial hemi-hypertrophy" or "Facial hemi-hypertrophy" or "Facial Gigantism" and 95 articles were identified. After manual reviewing and screening, 27 results were included in the analysis. Men are more commonly affected than women, with right side showing more involvement than the left side. Both hard and soft tissues are involved on the affected site. Reconstructive surgeries are usually planned after cessation of physiological growth. It includes orthognathic surgeries or osteotomies. Multiple soft tissue debulking procedures may be performed including excision of excess subcutaneous tissue and masticatory muscles, face-lift surgeries, lip reduction surgery, or parotidectomy. No malignant transformation has been reported in literature. The great variation of asymmetries caused by facial hemihypertrophies requires a combination and variety of sequential treatment procedures to gain adequate functional and cosmetic results. Hence, treatment of such malformation varies radically.